2002
DOI: 10.1016/s0005-2736(01)00445-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of the choline exchanger in Na+-independent Mg2+ efflux from rat erythrocytes

Abstract: Two types of Na(+)-independent Mg(2+) efflux exist in erythrocytes: (1) Mg(2+) efflux in sucrose medium and (2) Mg(2+) efflux in high Cl(-) media such as KCl-, LiCl- or choline Cl-medium. The mechanism of Na(+)-independent Mg(2+) efflux in choline Cl medium was investigated in this study. Non-selective transport by the following transport mechanisms has been excluded: K(+),Cl(-)- and Na(+),K(+),Cl(-)-symport, Na(+)/H(+)-, Na(+)/Mg(2+)-, Na(+)/Ca(2+)- and K(+)(Na(+))/H(+) antiport, Ca(2+)-activated K(+) channel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The specificity of this mechanism, however, is far from defined. Different cations including Ca 2+ or Mn 2+ , or anions such as HCO 3 − , Cl − , or choline, [147,148] have been reported to be utilized by this mechanism to extrude Mg 2+ . Hence, it remains unclear whether we are in the presence of distinct transport mechanisms, or in the presence of a transporter that can operate as an antiporter for cations or a sinporter for cations and anions based upon the experimental conditions.…”
Section: Mg2+ Transport Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…The specificity of this mechanism, however, is far from defined. Different cations including Ca 2+ or Mn 2+ , or anions such as HCO 3 − , Cl − , or choline, [147,148] have been reported to be utilized by this mechanism to extrude Mg 2+ . Hence, it remains unclear whether we are in the presence of distinct transport mechanisms, or in the presence of a transporter that can operate as an antiporter for cations or a sinporter for cations and anions based upon the experimental conditions.…”
Section: Mg2+ Transport Mechanismsmentioning
confidence: 99%
“…Hence, it remains unclear whether we are in the presence of distinct transport mechanisms, or in the presence of a transporter that can operate as an antiporter for cations or a sinporter for cations and anions based upon the experimental conditions. On the other hand, Ebel and collaborators [148] have suggested that Na + -independent Mg 2+ extrusion in red blood cells and hepatocytes occurs via the choline transporter, which can be inhibited rather specifically by cinchona alkaloids [148]. A second point of uncertainty is whether the Na + - independent pathway is activated by hormonal stimulation.…”
Section: Mg2+ Transport Mechanismsmentioning
confidence: 99%
“…2Na + /Mg 2+ exchange is probably driven by the transmembrane Na + gradient, as indicated by the requirement for both cell ATP and Na-K ATPase activity [36]. Recently, Ebel and Gunther characterised the Na + -dependent and Na + -independent Mg 2+ efflux in non-Mgloaded erythrocytes and described the participation of a choline/Mg 2+ exchanger in Mg 2+ efflux [37,38]. As regards Mg 2+ influx, it is well accepted that the entry of Mg + into the cell is basically driven by the electrochemical gradient, via channels and carriers [39].…”
Section: -Use Of Stable Isotopes In Cellular Mg Exchange Studiesmentioning
confidence: 99%
“…During this attempt, various types of transport systems previously found in different preparations (human, rat, and chicken erythrocytes, Ebel et al 2002;Günther and Vormann 1990;rat hepatocytes, Cefaratti et al 1998; rat ventricular myocytes, Ö dblom and Handy 1999; rat distal colon and caecum, Scharrer and Lutz 1990; ascites tumor cells, Günther et al 1986; fish enterocytes, Bijvelds et al 1996) (Ebel et al 2002) could not be carried out, because choline interferes at the Mg 2ϩ -selective microelectrode (McGuigan et al 1993). The presence of such an antiport seemed unlikely, because it would depend on the presence of extracellular choline.…”
Section: Temperature Dependence Of Mg 2ϩ Transportmentioning
confidence: 99%
“…Three forms of Na ϩ -independent cation transport have been described: a Ca 2ϩ /Mg 2ϩ antiport in liver cells of the rat (Cefaratti et al 1998), where it appears to be restricted to the apical membrane of the cells; a Mg 2ϩ /choline exchange in rat erythrocytes (Ebel et al 2002); and a H ϩ -driven Mg 2ϩ extrusion in form of a 1 Mg 2ϩ /2 H ϩ antiport in epithelial cells from the colon and cecum of the rat (Scharrer and Lutz 1990) and possibly in the rumen of sheep (Leonhard-Marek et al 1998;see, however, Schweigel et al 2000).…”
Section: Introductionmentioning
confidence: 99%